2018
DOI: 10.1111/jfbc.12669
|View full text |Cite
|
Sign up to set email alerts
|

Effect of boiling and roasting on the antidiabetic activity ofAbelmoschus esculentus(Okra) fruits and seeds in type 2 diabetic rats

Abstract: The present investigation aimed to study the effect of two culinary treatments (boiling and roasting) on the antidiabetic potential of Abelmoschus esculentus fruits and seeds in type 2 diabetic rats. Crude fiber, total phenolic content, and in vitro free radical scavenging capacity of the various culinary forms of the fruits and seeds were assessed. Streptozotoccin and high‐fat diet‐induced type 2 diabetes Wistar rats were randomly assigned to six groups of 10 rats each, and treated for 28 days with either met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Better antidiabetic and antioxidant effect of methanolic extracts compared to aqueous and ethanolic extracts were observed in this study (Ahmed & Kumar, 2016). (Nguekouo et al, 2018). Antidiabetic effects of this plant were similar to glibenclamide and glimperide sulfonylurea antidiabetic drugs.…”
Section: Effect Of Okra On Diabetesmentioning
confidence: 76%
“…Better antidiabetic and antioxidant effect of methanolic extracts compared to aqueous and ethanolic extracts were observed in this study (Ahmed & Kumar, 2016). (Nguekouo et al, 2018). Antidiabetic effects of this plant were similar to glibenclamide and glimperide sulfonylurea antidiabetic drugs.…”
Section: Effect Of Okra On Diabetesmentioning
confidence: 76%
“…Nguekouo et al (2018), in an in vivo study, showed that boiling and roasting do not change the antidiabetic potential of okra fruits and seeds [ 99 ]. Ortaç et al (2018) reported in an in vivo study that okra has a gastroprotective effect against ethanol and could decrease a gastric ulcer, as indicated by the biochemical and histopathological data.…”
Section: In Vivo Studies On the Health Benefits Of Okra And Its Comentioning
confidence: 99%
“…As reported in Table 1, some examples of current researches in animal models are moving in this direction [91,98,99,100,101,102].…”
Section: An Updated Overview Of Potential Beneficial Effects Assocmentioning
confidence: 99%
“…The effect of boiling and roasting on the antidiabetic activity of Abelmoschus esculentus (okra) fruits and seeds in type 2 diabetic rats was currently investigated by Nguekouo et al [101]: boiling and roasting do not significantly influence the antidiabetic potential. This research underlines how appropriate processing methods or culinary form should be established in order to increase the health-promoting properties of this plant [101].…”
Section: An Updated Overview Of Potential Beneficial Effects Assocmentioning
confidence: 99%